Effects of jasmonic acid on the feeding activity and reproductive performance of the two-spotted spider mites, Tetranychus Urticae Koch (Tetranychidae: Acari) - Nur Fariza M Shaipulah,; Nor Aida Rohayu Hashim,; Sharifah Masit’ah Syed Esa,; Lian, Chong Ju (Penerbit Universiti Kebangsaan Malaysia, 2022)
The two-spotted spider mite, Tetranychus urticae Koch, 1836 (Acari: Tetranychidae) is a common, yet major pest for rose cultivars. This study investigated the effect of jasmonic acid (JA), a key phytohormone in the mechanism of plant defence on the reproductive performance of T. urticae, and its damage to the leaves of roses (Rosa hybrida L.). The plants were initially treated with 10μM, 100μM and 1000μM, respectively of JA, and the female adults T. urticae were transferred to R. hybrida leaves after 1-hour and 12-hours of JA application. Results revealed that JA treatment at concentration of 100 μM (t4=4.51, P<0.05) and 1000 μM (t4 =10.82, P<0.001) reduced the infestation of T. urticae on leaves. Also, significantly fewer T. urticae eggs were observed after 1 hour (F4,15=32.869, P<0.001), and 12 hours (F4,15=44.149, P<0.001) of JA treatment. As compared to the control, a concentration of 1000μM JA exhibited the highest oviposition inhibition effect. Additionally, the 1-hour and 12-hours inhibition of oviposition (IOC50) values against T. urticae were 52.5 μM and 22.9 μM, respectively. These findings suggested that exogenous application of JA on R. hybrida was found to negatively affect the T. urticae feeding activity and its reproductive performance.